Project management at academic libraries: professional perception in Latin American countries - Cobo-Serrano, Silvia; Arquero-Avilés, Rosario (Revista General de Información y Documentación, 2017)
Library and information service professionals use project management techniques most frequently, the result of which infers an integrated knowledge on Management issues. This paper aims at analysing academic librarians’ perception on project management as a discipline in Latin American countries (Bolivia, Brazil, Chile, Colombia, Costa Rica, Cuba, Ecuador, Guatemala, Mexico, Panama, Paraguay, Peru, Puerto Rico and Venezuela). According to this, their opinions and professional experience will let us know the state of the art of this managerial technique. To that end, a quantitative and qualitative methodology has been based upon a questionnaire made up of 14 questions. The results are focused on the respondents’ geographic context and institutional affiliation, university training, professional experience based on projects as well as project management courses in Library and Information Science education.